Methodology For Inspection Of Elevator Systems After Strong Earthquakes And Their Field Testing Under Dynamic Loads - Olimkhon Khondamir; Mirhamidova E’zoza; Giyasov Shaxriyor (Zien Journals, 2024)
The study outlines a methodology for inspecting elevators after earthquakes and conducting field tests to assess their dynamic characteristics. The tests are carried out in two stages: sudden load release and vibrational impact. Seismometric equipment is used to measure displacements and accelerations of both the elevator and the building. This method helps identify the impact of building design features on elevator performance and enhances their safety in seismically active regions
Keywords: elevator; characteristics; stages